Guru sebagai Fasilitator dalam Learning by Doing: Relevansi Pragmatisme John Dewey bagi Pembelajaran Manajemen Pendidikan Islam - Masruri, Masruri; Jonny; Napitupulu, Alwi Muchtar; Faisal, Muhammad (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
This study addresses the need for Islamic Educational Management learning to move beyond conceptual mastery toward action competence through authentic experience. John Dewey’s pragmatism is employed because it positions experience and inquiry at the core of learning, and assesses educational experience through the principles of continuity and interaction. The objectives are to: (1) map Deweyan principles as a foundation for learning by doing in Islamic Educational Management; (2) operationalize the teacher/lecturer role as a facilitator; and (3) formulate a case/project-based learning model along with evaluative indicators. The method is qualitative library research using conceptual-philosophical analysis of Dewey’s primary works and supporting literature on experiential learning and facilitation. The findings indicate that learning becomes more effective when designed as a sequenced set of educational experiences, supported by guided reflection and evaluated using Dewey’s continuity–interaction criteria, preventing projects from becoming “mis-educative” activities